Application of the Biomechanical Approach in Learning Basic Long Jump Techniques for Students of Tamannyeleng Elementary School - Retno Farhana Nurulita (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study aims to analyze the effect of the application of a biomechanical approach on improving basic long jump technical skills in elementary school students. The biomechanical approach is used to help students understand the principles of efficient body movement based on the laws of force, speed, and angle of push. This study used a quasi-experimental method with a One Group Pretest–Posttest Design implemented at SD Inpres Tamannyeleng, Gowa Regency. The research sample consisted of 30 fifth-grade students (15 boys and 15 girls) who participated in six meetings, including pretest, learning implementation, and posttest. The research instruments included long jump skill observation sheets, motion video recordings, and field notes that were analyzed quantitatively and qualitatively. The results showed a significant increase in basic long jump technical skills after the application of the biomechanical approach. The average student score increased from 64.23 in the pretest to 78.90 in the posttest, with a difference of 14.67 points or 22.8%. The Paired Sample t-Test produced a t value = 9.214 and Sig. (2-tailed) = 0.000 (p < 0.05), which shows that the application of the biomechanical approach has a real effect on improving students' skills. Qualitatively, there was improvement in coordination, balance, and movement efficiency in each phase of the long jump—from the run-up to the landing. It can be concluded that the biomechanical approach is effective in physical education learning in elementary schools because it not only improves students' technical abilities but also fosters a scientific understanding of body movement and the simple application of biomechanical principles.